Biology - Brooker, Robert J.; Widmaier, Eric P.; Graham, Linda E.; Stiling, Peter D. (New York McGraw Hill, 2023)
"Over the course of these editions, the ways in which biology is taught have dramatically changed. We have seen a shift away from the memorization of details, which are easily forgotten, and a movement toward emphasizing core concepts and critical thinking skills. The previous edition of Biology strengthened skill development by adding two new features, called CoreSKILLS and BioTIPS, which are aimed at helping students develop effective strategies for solving problems and applying their knowledge in novel situations. In this edition, we have focused our pedagogy on the five core concepts of biology as advocated by "Vision and Change". In addition to core concepts, "Vision and Change" has strongly advocated the development of core skills (also called core competencies). Those skills are emphasized in this textbook. A key goal of this textbook is to bring to life the five core concepts of biology and the core skills. These concepts and skills are highlighted in each chapter with a "Vision and Change" icon, which indicates subsections and figures that focus on one or more of them. With regard to the scientific content in the textbook, the author team has worked with faculty reviewers to refine this new edition and to update the content so that students are exposed to the most current material. In addition to new pedagogical additions involving Core Concepts, Core Skills, and Modeling Challenges, every chapter has been extensively edited for clarity, presentation, layout, readability, modifications of artwork, and new and challenging end-of-chapter questions"--Provided by publisher.
Includes index.
AU Novero ( Recommending faculty) AY2022-2023
Keywords: Biology -- Textbooks